Estimation of time-space-varying parameters in dengue epidemic models - Karunia Putra Wijaya; Thomas Gotz (Indonesian Bio-Mathematical Society, 2017)
There are nowadays a huge load of publications about dengue epidemic models, which mostly employ deterministic differential equations. The analytical properties of deterministic models are always of particular interest by many experts, but their validity